1996
DOI: 10.1021/bi9524732
|View full text |Cite
|
Sign up to set email alerts
|

Adduction of the Human N-ras Codon 61 Sequence with (−)-(7S,8R,9R,10S)-7,8-Dihydroxy-9,10-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene:  Structural Refinement of the Intercalated SRSR(61,2) (−)-(7S,8R,9S,10R)-N6-[10-(7,8,9,10-Tetrahydrobenzo[a]pyrenyl)]-2‘-deoxyadenosyl Adduct from 1H NMR

Abstract: The structure of the (-)-(7S,8R,9S,10R)-N6-[10-(7,8,910-tetrahydrobenzo [a]pyrenyl)]-2'-deoxyadenosyl adduct at X6 of 5'-d(CGGACXAGAAG)-3'-5'-d(CTTCTTGTCCG)-3', derived from trans addition of the exocyclic N6-amino group of dA to (-)-(7S,8R,9R,10S)-7, 8-dihydroxy-9,10-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene [(-)-DE2], was determined using molecular dynamics simulations restrained by 369 NOEs from 1H NMR. This was named the SRSR(61,2) adduct, derived from the N-ras protooncogene at and adjacent to the nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
150
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(162 citation statements)
references
References 67 publications
11
150
1
Order By: Relevance
“…20,21 The 10R(Ϫ)-trans-anti adduct structure shown is essentially the same as that of the NMR solution structure of Zegar et al 22 determined in the same C[A*]A sequence context of codon 61 of the human N-ras gene.…”
Section: Adduct Structuressupporting
confidence: 66%
“…20,21 The 10R(Ϫ)-trans-anti adduct structure shown is essentially the same as that of the NMR solution structure of Zegar et al 22 determined in the same C[A*]A sequence context of codon 61 of the human N-ras gene.…”
Section: Adduct Structuressupporting
confidence: 66%
“…This adenine adduct of BPDE provides a distinct structural theme characterized by intercalative carcinogen insertion without displacement of the modified base pair, although the respective hydrogen bonds are destabilized more severely than in the trans-BPDE-N 2 -dG counterparts (57). Presumably because of these gradual differences in the extent of base pair disruption, the (Ϫ)-trans-BPDE-N 6 -dA adduct in the N-ras codon 61 sequence is excised in vitro at a slightly faster rate than the trans-BPDE-N 2 -dG adducts tested in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Two structures were aligned: the NMR structure of a DNA duplex that contains a trans-10R BaP DE-2 dA adduct (BaP-DNA) (20) and the x-ray crystal structure of human top1 covalently complexed with a double-stranded DNA substrate (7). The unadducted strand of the BaP-DNA was aligned with the scissile DNA strand in the top1 covalent complex.…”
Section: Dnamentioning
confidence: 99%
“…trans-opened BaP DE-2 adducts at N 6 of dA were selected because several NMR studies have shown that such adducts intercalate into the DNA without significant disruption of the DNA structure, whereas the previously studied (15) trans-opened BaP DE-2 adducts at N 2 of dG lie in the minor groove (16). trans-R dA adducts are intercalated toward the 5Ј side of the modified base (17)(18)(19)(20)(21). Although the evidence is less compelling for trans-10S-BaP DE-2 dA adducts, such adducts are thought to intercalate toward the 3Ј side of their adducted base (22,23).…”
mentioning
confidence: 99%